HOW PSYCHOLOGICAL FACTORS INFLUENCE ECONOMIC DECISION-MAKING, AND THE IMPLICATIONS FOR POLICY - Mudasir Ahmad Sofi; Irshad Ahmad Reshi; Dr. T. Sudha (PT. Radja Intercontinental Publishing, 2023)
Abstract Economic decision-making is often thought to be a purely rational process, with individuals making choices based on a careful analysis of costs and benefits. However, research has shown that psychological factors play a crucial role in shaping economic decisions. This paper reviews the literature on how psychological factors such as cognitive biases, emotions, and social influences influence economic decision-making. We also discuss the implications of these findings for policy-makers, highlighting the need for policies that take into account the role of psychological factors in shaping economic behavior.